Pengaruh Asam Amino Glutamin dan Arginin terhadap Pertumbuhan Anggrek Dendrobium sp. secara In Vitro : The Amino Acids effect of Glutamine and Arginine to Dendrobium sp Orchid Growth In Vitro - Rahmawati, Sinta; Rahayu, T.; Jayanti, G. E. (FMIPA UNISMA, 2025)
Dendrobium sp. orchids are very popular because of the variety of shapes, colors, and beauty of their flowers. Special handling is required for the growth of orchids, such as providing proper nutrition to stimulate their growth. The composition of the culture medium significantly impacts the development of the planlets. Glutamine and arginine are amino acids that are widely used in tissue culture media. The addition of glutamine to the culture media makes orchid planlets naturally nitrogen-induced which can increase planlet growth. While exogenously induced arginine can increase nitric oxide levels, thus stimulating planlet root growth. This study aims to determine the effect of the addition of amino acids glutamine and arginine in the culture medium on the growth of orchid planlets Dendrobium sp. This study used a completely randomized design with 7 treatments, namely control (MS), glutamine with concentrations of 50 mg/l, 75 mg/l, 100 mg/l; arginine 50 mg/l, arginine 75 mg/l and arginine 100 mg/l with 3 replicates each. Quantitative data were analyzed and tested ANOVA. The results showed that glutamine 50 mg/l treatment increased the planlet weight by 0.096 g, planlet height by 12.9 mm, and the number of leaves by 6 leaves. While glutamine 100 mg/l has the potential to increase the number of shoots with an average of 1.3. In the arginine treatment, the concentration of 50 mg/l increased the number of planlet roots by 2. Keywords: arginine, Dendrobium sp., glutamine, growth. ABSTRAK Anggrek Dendrobium sp. sangat populer karena memiliki beragam bentuk, warna serta keindahan bunganya. Penanganan khusus diperlukan untuk pertumbuhan anggrek, seperti memberi nutrisi yang tepat untuk merangsang pertumbuhannya. Komposisi media kultur secara signifikan berdampak pada perkembangan planlet. Glutamin dan arginin menjadi asam amino yang banyak digunakan dalam media kultur jaringan. Penambahan glutamin pada media kultur membuat planlet anggrek terinduksi nitrogen alami yang dapat meningkatkan pertumbuhan planlet. Sedangkan arginin yang diinduksi secara eksogen dapat meningkatkan kadar nitrit oksida, sehingga merangsang pertumbuhan akar planlet. Penelitian ini bertujuan untuk mengetahui pengaruh penambahan asam amino glutamin dan arginin dalam media kultur terhadap pertumbuhan planlet anggrek Dendrobium sp. Penelitian ini menggunakan Rancangan Acak Lengkap (RAL) dengan 7 perlakuan yaitu kontrol (MS), glutamin dengan konsentrasi 50 mg/l, 75 mg/l, 100 mg/l; arginin 50 mg/l, arginin 75 mg/l dan arginin 100 mg/l dengan masingmasing 3 ulangan. Data Kuantitatif dianalisis dan di uji Anova. Hasil penelitian menunjukkan bahwa perlakuan glutamin 50 mg/l meningkatkan berat planlet sebanyak 0,096 g, tinggi planlet sebesar 12,9 mm, dan jumlah daun sebanyak 6 helai daun. Sedangkan glutamin 100 mg/l berpotensi meningkatkan jumlah tunas dengan rerata sebanyak 1,3. Pada perlakuan arginin konsentrasi 50 mg/l meningkatkan jumlah akar planlet sebanyak 2. Kata kunci: arginin, Dendrobium sp., glutamin, pertumbuhan.